The Role of Teachers in 21st Century Learning During the Covid-19 Pandemic - Salmia Salmia; A. Muhammad Yusri (Indonesian Journal of Primary Education, 2021)
Learning activities during the Covid-19 Pandemic must continue to target the achievement of 21st century skills that integrate knowledge, skills, and attitudes, as well as mastery of technology, information and communication, even in Pandemic conditions like today. Therefore, this study aims to determine how teachers plan, carry out learning and guidance as well as to find out the type of assessment carried out. The type of research method used in this research was qualitative descriptive. This study did not use population and samples. The sample in qualitative research is called a theoretical sample. The research instruments used were observation, interview, and documentation. The data was collected from primary and secondary data sources. While the data analysis technique used consisted of 3 stages, namely: data collection, data reduction, data presentation, and data categorization. The results of this research showed that the teacher can design various learning plans in the form of assignments that can be done online, including video call, google class, zoom, or direct visits to students who did not have an internet network. In the assessment, the teacher could do it by making a journal or control card which was carried out by students while at home.